COVID-19: zaburzenia krzepnięcia i leczenie przeciwzakrzepowe u pacjentów hospitalizowanych na oddziale intensywnej terapii - Pluta, Jan; Cieniewicz, Agnieszka; Trzebicki, Janusz (Anestezjologia Intensywna Terapia, 2021)
Patients hospitalized in the intensive care unit (ICU) due to the COVID-19 experience a high incidence (up to 43%) of venous thromboembolic events. While laboratory findings in COVID-19-associated coagulopathy (CAC) show increased D-dimer and fibrinogen levels, the abnormalities in standard coagulation tests and platelet count are minimal. Recent studies suggest contribution of fibrinolysis shutdown to this phenomenon. Endothelial injury and alteration of its antithrombotic activity can lead to micro- and macrovascular thrombosis in the lungs, occurrence of which is associated with poor clinical outcome in critically ill patients with COVID-19. Additionally, the hypercoagulability induced by activation of coagulation pathways during the immune response to SARS-CoV-2 infection contributes to impaired organ perfusion. This, alongside with hypoxemia, leads to multiorgan failure. Various diagnostic regimens, some of which include global assays of haemostasis, are currently being published and discussed. Numerous guidelines and recommendations of scientific societies and groups of specialists have been published. However, there is no single optimal algorithm for anticoagulation treatment and monitoring specific to the ICU patients with COVID-19. The authors have attempted to summarize the data related to CAC and thrombotic disease and develop an algorithm consistent with the latest clinical practice guideline recommendations.